2000
DOI: 10.1016/s0014-5793(00)01407-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the gene product encoded by ORF UL56 of human cytomegalovirus into viral replication centers

Abstract: The highly conserved DNA-binding protein pUL56 of human cytomegalovirus (HCMV) was found to be predominantly localized throughout the nucleus as well as in viral replication centers of infected cells. The latter localization was abolished by phosphono acetic acid, an inhibitor of viral DNA replication. Immunofluorescence revealed that pUL56 co-localized in replication centers alongside pUL112^113 and pUL44 at late times of infection. By co-immunoprecipitations, a direct interaction with pUL44, a protein of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…5A, in cells infected with HD-UL51-NHA, pUL51 was enriched in the same nuclear compartments as pUL56 and pUL89. It has been shown that pUL56 localizes to viral DNA replication compartments (58) and, thus, we concluded that pUL51 is present in these subnuclear structures. In order to explore whether pUL51 does interact with pUL56 or pUL89, we applied affinity purification after infecting HFF with HD-UL51-SF, expressing pUL51 fused to the Strep-Flag tag.…”
Section: Hcmv Ul51 Mutantmentioning
confidence: 55%
“…5A, in cells infected with HD-UL51-NHA, pUL51 was enriched in the same nuclear compartments as pUL56 and pUL89. It has been shown that pUL56 localizes to viral DNA replication compartments (58) and, thus, we concluded that pUL51 is present in these subnuclear structures. In order to explore whether pUL51 does interact with pUL56 or pUL89, we applied affinity purification after infecting HFF with HD-UL51-SF, expressing pUL51 fused to the Strep-Flag tag.…”
Section: Hcmv Ul51 Mutantmentioning
confidence: 55%
“…Direct interaction of the pUL56 NLS with importin a implied that nuclear translocation is mediated by the importin-dependent pathway. Furthermore, it was found that pUL56 is predominantly localised in viral replication centers at late times of infection ( Figure 3) [43]. In these replication centers pUL56 co-localises alongside pUL112-113 as well as pUL44, proteins known to be involved in DNA replication.…”
Section: Introductionmentioning
confidence: 95%
“…The viral protein responsible for DNA binding during the packaging process, UL56, is found within replication compartments. UL56 localization to replication compartments is dependent on viral DNA synthesis, and UL56 may interact with UL44 within replication compartments (Giesen et al, 2000). Furthermore, it has been speculated that packaging of viral DNA into capsids is responsible for the movement of newly synthesized viral DNA from the periphery of replication compartments to the interior of replication compartments (Strang et al, 2012b).…”
Section: Structures Associated With Hcmv Replication: Nucleoli Cajalmentioning
confidence: 99%